BENANG PENGIKAT WACANA BAHASA SUNDA - Zaenal Arifin (Kajian Linguistik dan Sastra, 2005)
The study is about discourse relators in Sundanese. The data of Sundanese expressions will be analyzed using formal discourse analysis, focusing on cohesion. The result shows that there are two kinds of discourse relators in Sundanese which are grammatically and lexically characterized. The grammatically characterized discourse relators are reference, substitution, ellipsis, and conjunctive relation. The latter comprises several types and sub-types. Meanwhile, the lexically characterized discourse relators consist of six kinds: repetition, synonym, antonym, hyponym, mernym, and collocation. This latter kind also includes several types and sub-types. The typically unique discourse relators in Sundanese are cataphoraic pronoun of intra-phrase, inter-sentence, and inter-paragraph. The inter-paragraph cataphoraic pronoun can be used if there is not a new topic between the refernce and the referred pronoun. In Sundanese, in order restate something previously atated, we can use the repetition of the same form or the repplacement with co-referential form followed by demonstratives ieu 'this, eta 'that close', and itu 'that far'. Moreover, the referential statement or replacement can be followed by the difinite demonstratives teh 'that' and tea 'that'.Key words: discourse relators, grammatical, and lexical cohesive device